TYPES OF GEODETIC WORKS IN THE CONSTRUCTION OF HIGH-RISE BUILDINGS AND STRUCTURES (British Journal of Global Ecology and Sustainable Development, 2022)
This article provides information on the order and types of geodetic works in the construction of multi-storey buildings.